SISTEM INFORMASI PENJUALAN PT. CATUR NAGA STEELINDO - Satrio Broto; Rahmad Fitri; Baharini Kurnia Putri; Fatma Nurazizah (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
PT. Catur Naga Steelindo, which still uses a manual system, often causes problems within the company, including data duplication, difficulty in obtaining purchase data, sales data and delays in reporting. The problems that arise are because the company has not optimized the use of computers so that the information produced is more accurate. It takes a sales information system that can reduce the existing problems. The purpose of this research is to design a sales application for companies in processing data as a means to facilitate data processing and can be accessed anywhere and can be used on any device. The results achieved from making a sales information system can improve the performance of a company to be more effective and efficient in performing computerized data processing